ANIMASI DALAM PEMBELAJARAN IPS DENGAN MODEL KOOPERATIF TIPE JIGSAW : PENGARUHNYA TERHADAP HASIL BELAJAR DAN NURTURANT EFFECT - Sugiantoro Sugiantoro (LPPM STKIP PGRI Sidoarjo, 2023)
This research was conducted to determine the significant effect of the jigsaw type cooperative learning model assisted by animation on class VII students of junior high school. The population of this study were all students of class VII SMP. The number of respondents is 30 students where the respondents are the population as well as the research sample. This research is a descriptive quantitative research with one group pretest-posttest design. From the results of the analysis above: (1) Differences in learning outcomes in the cooperative learning model with the animation-assisted jigsaw strategy can be seen from the average pretest score (69.57), and posttest score (84.80) and individual completeness at pretest (43%) and posttest (80%), while classical learning completeness reaches more than 80% so that it reaches the Minimum Completeness Criteria, 2) Student responses to the jigsaw-type cooperative learning model assisted by animation obtained were 87% of students liked the classroom atmosphere, and 96% of students liked the way the teacher taught the material, and 88% of students considered themselves helped and got more opportunities and 89% of students feel that they have had a good opportunity in expressing ideas, responding to questions, asking questions, and presenting work results so as to foster self-confidence, being able to think critically, being open, self-motivated, cooperative, and responsible, 3) there is the effectiveness of implementing the type cooperative learning model jigsaw in social studies learning as evidenced by the percentage of agreement obtained from two observers of 97%.